Progress in upscaling Miscanthus biomass production for the European bio‐economy with seed‐based hybrids. Issue 1 (23rd May 2016) - Clifton‐Brown, John; Hastings, Astley; Mos, Michal; McCalmont, Jon P.; Ashman, Chris; Awty‐Carroll, Danny; Cerazy, Joanna; Chiang, Yu‐Chung; Cosentino, Salvatore; Cracroft‐Eley, William; Scurlock, Jonathan; Donnison, Iain S.; et al.
Abstract: Field trials in Europe with Miscanthus over the past 25 years have demonstrated that interspecies hybrids such as M.  ×  giganteus ( M  ×  g ) combine both high yield potentials and low inputs in a wide range of soils and climates. Miscanthus hybrids are expected to play a major role in the provision of perennial lignocellulosic biomass across much of Europe as part of a lower carbon economy. However, even with favourable policies in some European countries, uptake has been slow. M  ×  g, as a sterile clone, can only be propagated vegetatively, which leads to high establishment costs and low multiplication rates. Consequently, a decade ago, a strategic decision to develop rapidly multiplied seeded hybrids was taken. To make progress on this goal, we have (1) harnessed the genetic diversity in Miscanthus by crossing and progeny testing thousands of parental combinations to select several candidate seed‐based hybrids adapted to European environments, (2) established field scale seed production methods with annual multiplication factors >1500×, (3) developed the agronomy for establishing large stands from seed sown plug plants to reduce establishment times by a year compared to M  ×  g, (4) trialled a range of harvest techniques to improve compositional quality and logistics on a large scale, (5) performed spatial analyses of yield potential and land availability to identify regional opportunities across Europe and doubled the area within the bio‐climatic envelope, (6) considered on‐farm economic, practical and environmental benefits that can be attractive to growers. The technical barriers to adoption have now been overcome sufficiently such that Miscanthus is ready to use as a low‐carbon feedstock in the European bio‐economy.